Tunable performance of indium tin oxide-zinc oxide as Q-switcher - Zalkepali, N.U.H.H.; Awang, N.A.; Ghosh, B.K.; Mohamad, K.A.; Alias, A.; Mahmud, N.N.H.E.N.; Zamri, A.Z.M.; Muhammad, N.A.M. (Elsevier, 2023)
This work successfully demonstrated the tunable performance of a Q-switched pulse erbiumdoped fiber laser (QPEDFL) using Indium Tin Oxide-Zinc Oxide (ITO-ZnO)-based SA. The ITOZnO is a material growth between transparent conducting oxides and transition metal oxides on a glass slide. The mechanical exfoliation technique is applied to serve the ITO-ZnO as SA and inserted in a single-ring cavity design. The QPEDFL in a single ring cavity gives the repetition rate, pulse width, average output power, pulse energy, and SNR of 38.49 kHz, 5.50 µs, 0.47 mW, 12.72 nJ, and 64.20 dB, respectively. Furthermore, the ITO-ZnO as SA provides a tuning range of 30.40 nm. By tuning the TBF, the wavelength changes from 1531.60 nm to 1562.0 nm, causing the pulse repetition rate and pulse width of the QPEDFL to vary from 41.50 kHz to 17.20 kHz, and 4.22 µs to 10.05 µs, respectively. According to the results obtained, it can confidently say the suggested pulse laser has potential in the application of optical communication systems as a light source.